Kant's lectures = Kants Vorlesungen - Dörflinger, Bernd, 1953-; La Rocca, Claudio; Louden, Robert (De Gruyter, 2015)
Although they were not written by Kant himself, the transcripts of his lectures constitute an important source for philosophical research today. The contributions presented in this volume discuss the authenticity and significance of these transcripts. Theyshed light ondifferent philosophical questions related to Kant's philosophy and provide new insights that, if looking at Kant's published writings alone, we would not be able to gain.